Adjunctive Systemic Azithromycin with Nonsurgical Periodontal Treatment: Effects on Clinical Parameters in Smokers with Periodontitis - Melike Camgoz; Nilsun Bagis; Elif Unsal (University of Zagreb. School of Dental Medicine, 2023)
Objectives: Smokers with periodontitis are therapeutically challenging. Azithromycin (AZM) may be used as an adjunct to periodontal treatment. The aim of this randomized, double-blind, controlled clinical study was to determine the effect of azithromycin in shallow, moderate, and deep pocket depths in smokers when combined with non-surgical periodontal treatment. Material and methods: Forty-nine patients who smoked at least 20 cigarettes per day for more than 5 years were included in the study; however only 40 completed it. The number of teeth, plaque index (PI), gingival index (GI), PPD, CAL, bleeding on probing (BOP) and gingival recession were recorded at baseline and months 1, 3 and 6. The pocket depths (PD) were grouped as shallow, moderate, and deep. Twenty-four patients assigned to the AZM+ (test) group received AZM (500 mg tablets) once a day for 3 days, beginning on the first day of SRP. Results: The decline in the total number of pockets in all groups was statistically significant from baseline to 1 st , baseline to 3 rd , baseline to 6 th ; and from 1 st to 3 rd and 1 st to 6 th months. There was a statistically significant increase in the number of shallow pockets between baseline and 3 rd , baseline and 6 th ; and 1 st and 6 th months (p=0.000) for both groups. Conclusion: Antibiotic administration significantly increased the number of shallow pockets at all time points. However, larger scale controlled clinical studies are needed to verify the efficiency of AZM in smoker periodontitis patients.